2011
DOI: 10.1177/155005941104200411
|View full text |Cite
|
Sign up to set email alerts
|

A Large Clinical Study on the Ability of Stroke Patients to Use an EEG-Based Motor Imagery Brain-Computer Interface

Abstract: Brain-computer interface (BCI) technology has the prospects of helping stroke survivors by enabling the interaction with their environ ment through brain signals rather than through muscles, and restoring motor function by inducing activity-dependent brain plasticity. This paper presents a clinical study on the extent of detectable brain signals from a large population of stroke patients in using EEG-based motor imagery BCI. EEG data were collected from 54 stroke patients whereby finger tapping and motor image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
157
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(166 citation statements)
references
References 32 publications
6
157
0
3
Order By: Relevance
“…This self-regulation of brain activity during MI can be supported by providing visual or proprioceptive feedback about the current user's brain state (Boe et al, 2014;Dobkin, 2004;Gomez-Rodriguez et al, 2011) using brain-computer interfaces (BCIs) or brain-robot interfaces (BRIs), respectively (Birbaumer and Cohen, 2007;Fetz, 2007;Wolpaw, 2007). First studies applying these approaches in stroke rehabilitation are promising (Ang et al, 2011(Ang et al, , 2014Buch et al, 2008Buch et al, , 2012Gomez-Rodriguez et al, 2011;Prasad et al, 2010;Ramos-Murguialday et al, 2013;Shindo et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…This self-regulation of brain activity during MI can be supported by providing visual or proprioceptive feedback about the current user's brain state (Boe et al, 2014;Dobkin, 2004;Gomez-Rodriguez et al, 2011) using brain-computer interfaces (BCIs) or brain-robot interfaces (BRIs), respectively (Birbaumer and Cohen, 2007;Fetz, 2007;Wolpaw, 2007). First studies applying these approaches in stroke rehabilitation are promising (Ang et al, 2011(Ang et al, , 2014Buch et al, 2008Buch et al, , 2012Gomez-Rodriguez et al, 2011;Prasad et al, 2010;Ramos-Murguialday et al, 2013;Shindo et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Several single-case studies have reported improved motor function in the context of SMR-BMI applications (Broetz et al, 2010;Caria et al, 2011;Daly et al, 2009). Larger case-series documented recovery along various modalities, eg, reappearance of EMG signals in the paralyzed hand, decrease in resting threshold of MEPs elicited from the ipsilesional motor cortex, as well as improved clinical motor function scores (Ang et al, 2011;Prasad et al, 2010;Shindo et al, 2011). Further studies have suggested that ERD feedback coupled with somatosensory stimuli might be more effective for functional recovery than simple visual stimuli .…”
Section: Bmi Motor Rehabilitation and Its Outcomementioning
confidence: 92%
“…This motivated the use of BrainComputer-Interface (BCI) to detect motor imagery with robotic feedback for stroke rehabilitation [10], [11], [12]. In this work, the Haptic Knob is used for the stroke patient to attempt to open or close fingers or rotate their forearms in order to help them acquire skills necessary for fine object manipulation.…”
Section: Introductionmentioning
confidence: 99%